The silence of the archive - Thomas, David 1950-; Fowler, Simon; Johnson, Valerie (Archivist); Gilliland, Anne J.; Yeo, Geoffrey (Cambridge, United Kingdom Facet Publishing, 2017)
Records and archives, whether maintained by individuals, organizations, or community groups, are important sources that provide evidence of, and information about, the course of their creators and the environment in which those actions occurred. But at time incompleteness can be frustrating to those who seek to use them. The authors explore the societal impact of records and archives, and the consequences that result when records are absent or uniformative. They look at the ways in which the lack of comprehensive record keeping creates "silences" which, though unsettling to some, are sometimes inevitable.
Introduction to the series / Geoffrey Yeo -- Foreword /Anne J. Gilliland -- Enforced silences / Simon Fowler -- Inappropriate expectations / Simon Fowler -- The digital / David Thomas -- Dealing with the silence / Valerie Johnson -- Imagining archives / David Thomas -- Solutions to the silence / Valerie Johnson -- Are things getting better or worse? / David Thomas.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Archives -- Acquisitions; Appraisal of archival materials; Records retention; Electronic books